(untitled) (The Review of Diabetic Studies, 2025)
Background: Clinical healthcare environments are inherently complex and high-risk, exposing patients, healthcare professionals, and support staff to a wide range of safety threats. These risks include healthcare-associated infections, procedural errors, occupational injuries, environmental hazards, and workplace violence. While patient safety initiatives have expanded globally, many risk management frameworks remain profession-specific, often overlooking the interconnected roles of Dentistry, Nursing, and Health Assistant/Security personnel in maintaining safe clinical environments. Objective: This paper aims to develop and examine an interprofessional risk assessment and safety management model that explicitly integrates Dentistry, Nursing, and Health Assistant/Security roles within clinical healthcare settings. Methods: A narrative review of international literature was conducted, drawing on evidence from healthcare safety, infection control, occupational health, and security management domains. Based on the reviewed evidence, a conceptual interprofessional framework was developed to define role-specific and shared responsibilities in risk identification, assessment, mitigation, and reporting. Results: The findings highlight that Dentistry is primarily exposed to procedural and infection-related risks, Nursing plays a central role in continuous patient monitoring and safety coordination, and Health Assistant/Security personnel are critical for managing environmental risks, access control, and violence prevention. When these roles operate within a coordinated framework, safety gaps are reduced, communication improves, and proactive risk mitigation becomes feasible. Conclusion: An interprofessional approach to risk assessment and safety management is essential for modern clinical healthcare settings. Integrating Dentistry, Nursing, and Health Assistant/Security roles within a unified safety model enhances patient protection, safeguards healthcare workers, and strengthens organizational resilience. This model provides a foundation for future empirical research and policy development aimed at improving clinical safety outcomes.